DNA‐Nanotechnologie. Issue 3 (4th June 2013) - Simmel, Friedrich C.
<x xml:space="preserve">Abstract</x> For the past two decades the extraordinary molecular recognition properties of DNA molecules have been used for the creation of artificial molecular structures. Following the initial production of simple molecular objects and lattices, with the recent invention of the DNA origami technique the complexity of these structures has considerably increased. Now the construction of almost arbitrary molecular nanostructures from DNA in two and even three dimensions is feasible – and first concrete applications in biomedicine and nanotechnology are in reach. In addition to static molecular structures, also dynamical systems such as molecular machines, molecular motors, and molecular computers can be realized. The combination of these functions within integrated systems currently leads to the development of first molecular "robots" and assembly lines for nanotechnology.